Sparse dynamic reorganising fuzzy neural networks - Zhou, Jair Weigui (2017)
Fuzzy logic systems can broadly be grouped into two main types; namely: linguistic fuzzy systems (Mamdani) and precise fuzzy systems (Takagi-Sugeno-Kang). Fuzzy neural systems have been extensively researched and utilized in recent years because of their learning capability and interpretability in data modelling.